Phenotypic plasticity in a soybean cultivar with indeterminate growth type - Balbinot Junior, Alvadi Antonio; Oliveira, Maria Cristina Neves de; Franchini, Julio Cezar; Debiasi, Henrique; Zucareli, Claudemir; Ferreira, André Sampaio; Werner, Flavia (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate how branch and stem variables contribute to grain yield in individual soybean (Glycine max) plants, cultivated at different planting densities, in a modern cultivar with indeterminate growth type. A field experiment was carried out during the 2013/2014 and 2014/2015 crop seasons, in a randomized complete block design with 12 replicates, using the cultivar NK7059 RR at four planting densities: 135, 235, 315, and 440 thousand plants per hectare. Grain yield per plant was evaluated and represented phenotypic plasticity, while the number of branches per plant, percentage of grain production in branches, and separate yield components from branches and stems were considered as the independent variables. The number of pods in branches per plant was found to be the most important variable for soybean plasticity. In addition, the number of pods per plant on stems, number of branches per plant, and the percentage of grain production in branches were also associated with plasticity. Contrastingly, the number of grains per pod and the mass of a thousand grains in the branches and stems contributed little to plasticity in ’NK7059 RR’ soybean.